ANALYSIS OF HOSPITAL ANTIBIOTIC PRESCRIPTIONS AFTER THE IMPLEMENTATION OF STEWARDSHIP: A RETROSPECTIVE OBSERVATIONAL STUDY IN TWO HOSPITALS IN NORTH-EASTERN SICILY - Salvatore Coppolino; Veronica Crucitti; Febronia Federico; Emanuele Leotta; Nadia Caporlingua (OPI Napoli, 2023)
Introduction: Antimicrobial resistance is a global problem caused by the inappropriate use of antibiotics. To combat this phenomenon, multidisciplinary antimicrobial stewardship programmes have been initiated, the primary objectives of which include improving both the level of appropriateness of prescription and clinicians' awareness of the correct use of antibiotics. Objective/Purpose: The objective of the work was to conduct an analysis of antibiotic consumption at hospital level to assess the appropriateness of antibiotic prescription in a number of Operational Units. Method: From 01/01/2021 to 31/12/2022, data were extracted from the Pharmacy Operational Unit's management software on the dispensing of antibiotics (injectable and oral use), the Defined Daily Doses, and the number of dosage units dispensed to the General Medicine, Intensive Care, General Surgery and Neurorehabilitation Operational Units of two hospitals. Results: Total antibiotic consumption was 7,845 dosage units in 2021 and 10,182 in 2022. The comparison of the defined daily dose values (4,565,485 in 2021 and 5,079,671 in 2022) is indicative of the use of antibiotics with different dosages, with a percentage increase of 11.3%. A comparison was also made between the Defined Daily Doses/100 bed-days delivered in 2021 and the regional and national figures, yielding a significantly lower figure than these latter figures. Conclusions: The loss of antibiotic efficacy threatens to throw healthcare systems into crisis, leading to in an increase in morbidity and mortality from infections. The implementation of antimicrobial stewardship programmes remains, at present, the best tool to harness in order to curb the phenomenon of antimicrobial resistance. There is therefore a need for increasingly specialised professionals in the field of infectious diseases. Nurses and pharmacists play a crucial role in antimicrobial stewardship programmes, as they collaborate not only in the implementation of antimicrobial guidelines, but also in the review of individual patient regimens in order to optimise treatment and in the training of healthcare personnel on the appropriate use of antimicrobials.